Teaching the Entrepreneurial Mindset to Engineers - Bosman, Lisa (Springer International Publishing, 2018)
This book provides engineering faculty members and instructors with a base understanding of why the entrepreneurial mindset is important to engineering students and how it can be taught. It helps advance entrepreneurship education for all engineering students, and equips educators with tools and strategies that allow them to teach the entrepreneurial mindset. Divided into four parts, this book explores what the entrepreneurial mindset is, and why it is important; shows how to get started and integrate the mindset into existing coursework so that curricula can focus on both technical/functional concepts and entrepreneurial ones as well; guides readers through the growing multitude of conferences, journals, networks, and online resources that are available; and provides solid examples to get the reader started. This book is an important resource for engineering educators as they learn how to remain competitive and cutting-edge in a field as fast-moving and dynamic as engineering. Explores what the entrepreneurial mindset is and why it is important for engineers; Offers a structured approach for integrating the entrepreneurial mindset into existing engineering courses; Provides more than 25 examples and exercises.